2020
DOI: 10.3390/molecules25030456
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic Derivatives as Antitubercular Agents: Characterization by Quantitative Structure–Activity Relationship Studies

Abstract: Tuberculosis, caused by Mycobacterium tuberculosis (Mtb), remains one of the top ten causes of death worldwide and the main cause of mortality from a single infectious agent. The upsurge of multi- and extensively-drug resistant tuberculosis cases calls for an urgent need to develop new and more effective antitubercular drugs. As the cinnamoyl scaffold is a privileged and important pharmacophore in medicinal chemistry, some studies were conducted to find novel cinnamic acid derivatives (CAD) potentially active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Hence, it appears that several derivatives (7-24) from this chemical class can act in different biological systems (see Table 1). (Peperidou et al, 2017) Antimicrobial Mycobacterium smegmatis (Teixeira et al, 2020) Enzymatic inhibition Lipoxygenase (LOX) (Landberg et al, 2020) Enzymatic inhibition Acetylcholinesterase (AchE) Ghafary et al, 2020) Source: Authors (2021).…”
Section: Bioactivity Of Cinnamic Acid and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it appears that several derivatives (7-24) from this chemical class can act in different biological systems (see Table 1). (Peperidou et al, 2017) Antimicrobial Mycobacterium smegmatis (Teixeira et al, 2020) Enzymatic inhibition Lipoxygenase (LOX) (Landberg et al, 2020) Enzymatic inhibition Acetylcholinesterase (AchE) Ghafary et al, 2020) Source: Authors (2021).…”
Section: Bioactivity Of Cinnamic Acid and Its Derivativesmentioning
confidence: 99%
“…CA is recognised as an intermediate in the synthesis of many active compounds in plant species and also exhibits potent inhibition of protease enzymes, such as lipoxygenase. Several studies have shown that other acids found in nature (caffeic (2), ferulic (3), and pcoumaric (5) acids) and the phenolic kinematic derivatives, including those containing amide groups, display properties that contribute to the reduction and/or inhibition of free radicals and reactive oxygen species (ROS), which lead to the minimisation of the incidence of numerous degenerative, infectious, cardiovascular diseases, among others (Teixeira et al, 2020).…”
Section: The Biosynthesis Of Cinnamic Acid and Its Derivatives In Plant Speciesmentioning
confidence: 99%
“…In the last 10 years, interest in CA and its derivatives (esters, amides, aldehydes and alcohols) [ 5 ] has increased because of its many pharmacological activities, such as antituberculosis [ 6 , 7 , 8 , 9 ], antiviral [ 10 ], anticancer [ 11 , 12 , 13 , 14 , 15 , 16 ], mammary (MCF-7) and prostate (PC-3) inhibition, neoplastic cell growth, apoptosis inducement [ 17 , 18 , 19 ], anticholesterolemic [ 20 , 21 , 22 , 23 ], cardioprotective [ 24 ], antioxidant [ 25 , 26 , 27 , 28 ], anti-inflammatory [ 2 , 29 , 30 , 31 , 32 ], hepatoprotective [ 33 , 34 , 35 ], antidiabetic [ 36 , 37 , 38 ], antimalarial [ 39 ], anxiolytic [ 40 ], central nervous system depressant [ 41 ], neuroprotective [ 42 , 43 , 44 , 45 , 46 ], larvicidal agent [ 47 , 48 , 49 , 50 , 51 ], anti-leishmania [ 52 ], cosmetic […”
Section: Introductionmentioning
confidence: 99%
“…In consequence, cinnamic acid and its derivatives are promising starting point on the path from molecules to drugs due to their low toxicity and wide spectrum of anti-infective potential [ 19 , 20 ]. In the search for new pharmacologically active agents a number of cinnamic acid anilides were prepared and tested to specify their antifungal, antibacterial, and antimycobacterial activity profile [ 21 , 22 , 23 , 24 , 25 ]. Based on the antileishmanial activity of dihydroxycinnamic compounds, where the catechol-like moiety is frequently involved in a metal (Mn 2+ ) coordination bond by one of its hydroxyl groups, we proposed the introduction of halogen into the molecular structure of N -arylcinnamammides.…”
Section: Introductionmentioning
confidence: 99%